Troutville: Where People Discuss Fairness Issues - Asada, Yukiko; Urquhart, Robin; Brown, Marion; Warner, Grace; McNally, Mary; Murphy, Andrea (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
Context. Public engagement efforts in health policy have posed many value-laden questions, yet those that appreciate the complexity and diversity of the concept of health equity are rare. We introduce the Fairness Dialogues, a new method for deliberating health equity among the general public. We provide its theoretical underpinning and present its empirical illustration and qualitative assessment. Methods. Primarily informed by the scholarship of deliberation, we designed the Fairness Dialogues, featured by reason-giving and inclusive group deliberation using a hypothetical scenario (the town of Troutville) that presents carefully designed, simple, open-ended cases focusing on a chosen equity and fairness issue. To assess whether the Fairness Dialogues encourages reflective views, we conducted a qualitative investigation by focusing on fairness and unfairness of inequalities in life expectancy. Findings. Our results revealed the complex intuitions that people have and their curiosity, patience, and willingness to scrutinize them in-depth through a small group dialogue. Intuitions shared by our study participants are similar to those presented in the scholarly philosophical literature. Conclusions. The Fairness Dialogues is a promising method to incorporate the public’s views into policy-making involving value judgment and to develop the capacity of the public to discuss value-laden questions in a reflective and inclusive manner.